FIP-fve Stimulates Cell Proliferation and Enhances IL-2 Release by Activating MAP2K3/p38α (MAPK14) Signaling Pathway in Jurkat E6-1 Cells - Gu, Kefei; Wang, Tan; Peng, Liying; Zhao, Yueliang (Frontiers in Nutrition, 2022)
FIP-fve, a fungal fruiting body protein from Flammulina velutipes, has potential immunomodulatory properties. Here, we investigated the immunomodulation mechanism of FIP-fve in Jurkat E6-1 cells by conducting cell viability assay and IL-2 release assay. Kinase inhibitors experiment and proteomics analysis were also involved in the mechanism study. It was found that FIP-fve stimulated cell proliferation and enhanced IL-2 secretion in a dose-dependent manner in Jurkat E6-1 cells. Unbiased high-throughput proteomics analysis showed that 4 T cell immune activation markers including ZAP-70, CD69, CD82 and KIF23 were upregulated in response to FIP-fve treatment. Further pathway analysis indicated that MAP2K3/p38 pathway related proteins including MAP2K, p38, ELK, AATF, FOS, and JUN-B were unregulated. In addition, losmapimod (p38 inhibitor) and gossypetin (MAP2K3 inhibitor) inhibited FIP-fve enhanced cell proliferation and IL-2 release in Jurkat E6-1 cells. Our results demonstrate that FIP-fve stimulates cell proliferation and enhances IL-2 secretion through MAP2K3/ p38α activation.